Genome-Wide Transcriptional and Post-transcriptional Regulation of Innate Immune and Defense Responses of Bovine Mammary Gland to Staphylococcus aureus - Fang, Lingzhao; Hou, Yali; An, Jing; Li, Bingjie; Song, Minyan; Wang, Xiao; Sørensen, Peter; Dong, Yichun; Liu, Chao; Wang, Yachun; Zhu, Huabin; Zhang, Shengli; et al. (Frontiers in Cellular and Infection Microbiology, 2016)
Staphylococcus aureus (S. aureus) is problematic for lactating mammals and public health. Understanding of mechanisms by which the hosts respond to severe invasion of S. aureus remains elusive. In this study, the genome-wide expression of mRNAs and miRNAs in bovine mammary gland cells were interrogated at 24h after intra-mammary infection (IMI) with high or low concentrations of S. aureus. Compared to the negative control quarters, a total of 194 highly-confident responsive genes were identified in the quarters with high concentration (109cfu/mL) of S. aureus, which were predominantly implicated in pathways and biological processes pertaining to innate immune system, such as cytokine-cytokine receptor interaction and inflammatory response. In contrast, only 21 highly-confident genes were significantly differentially expressed in face of low concentration (106cfu/mL) of S. aureus, which slightly perturbed the cell signaling and invoked corresponding responses like vasoconstriction, indicating limited perturbations and immunological evading. Additionally, the significant up-regulations of bta-mir-223 and bta-mir-21-3p were observed in the quarters infected by high concentration of S. aureus. Network analysis suggested that the two miRNAs’ pivotal roles in defending hosts against bacterial infection probably through inhibiting CXCL14 and KIT. The significant down-regulation of CXCL14 was also observed in bovine mammary epithelial cells at 6 and 24h post infection of S. aureus (108cfu/mL) in vitro. Integrated analysis with QTL database further suggested 28 genes (e.g. CXCL14, KIT and SLC4A11) as candidates of bovine mastitis. This study first systematically revealed transcriptional and post-transcriptional responses of bovine mammary gland cells to invading S. aureus in a dosage-dependent pattern, and highlighted a complicated responsive mechanism in a network of miRNA-gene-pathway interplay.